Return to Work sebagai Bentuk Jaminan Kecelakaan Kerja di Badan Penyelenggara Jaminan Sosial (BPJS) Ketenagakerjaan - Dian Ayu Nurul Muthoharoh; Danang Ari Wibowo (CV Rewang Rencang, 2020)
Employees have rights that are protected by law. The rights of employees who are the focus of this paper are the right to occupational safety and health. To protect these rights, the government provides social security in the form of Work Accident Insurance (JKK) for employees who have occupational illnesses and work accidents. Work accidents can have serious impacts such as defects or potential defects that certainly affect the ability to work. Return to Work is an extension of benefits on the guarantee of work accidents, namely in the form of assistance to participants who have a work accident that causes disability or potential disability, ranging from the occurrence of accidents to be able to return to work. The purpose of this program is to ensure employees who have a work accident can return to work without facing the risk of termination due to their disability.